Cholinergic and Non-Cholinergic Projections from the Pedunculopontine and Laterodorsal Tegmental Nuclei to the Medial Geniculate Body in Guinea Pigs - Motts, Susan D.; Schofield, Brett R. (Frontiers in Neuroanatomy, 2010)
The midbrain tegmentum is the source of cholinergic innervation of the thalamus and has been associated with arousal and control of the sleep/wake cycle. In general, the innervation arises bilaterally from the pedunculopontine tegmental nucleus (PPT) and the laterodorsal tegmental nucleus (LDT). While this pattern has been observed for many thalamic nuclei, a projection from the LDT to the medial geniculate body (MG) has been questioned in some species. We combined retrograde tracing with immunohistochemistry for choline acetyltransferase (ChAT) to identify cholinergic projections from the brainstem to the MG in guinea pigs. Double-labeled cells (retrograde and immunoreactive for ChAT) were found in both the PPT (74%) and the LDT (26%). In both nuclei, double-labeled cells were more numerous on the ipsilateral side. About half of the retrogradely labeled cells were immunonegative, suggesting they are non-cholinergic. The distribution of these immunonegative cells was similar to that of the immunopositive ones: more were in the PPT than the LDT and more were on the ipsilateral than the contralateral side. The results indicate that both the PPT and the LDT project to the MG, and suggest that both cholinergic and non-cholinergic cells contribute substantially to these projections.